Pharmacokinetics and biosafety evaluation of a veterinary drug florfenicol in rainbow trout, Oncorhynchus mykiss (Walbaum 1792) as a model cultivable fish species in temperate water - Mallik, Sumanta Kumar; Shahi, Neetu; Pathak, Richa; Kala, Krishna; Patil, Prasanna Kumar; Singh, Bhupendra; Ravindran, Rajisha; Krishna, Nanitha; Pandey, Pramod Kumar (Frontiers in Pharmacology, 2023)
In two experimental trials; florfenicol pharmacokinetics following a single dose oral administration at 15 mg kg−1 fish body weight and biosafety through extended medicated feeding were studied in the rainbow trout, Oncorhynchus mykiss. The pharmacokinetic trial was conducted for 5 days, whereas the biosafety experiment lasted for a 30-day safety margin followed by a 20-day residual period analysis at 3, 5 and 10 times greater than the therapeutic dose 10 mg kg−1 biomass day−1. Cmax µg kg−1 calculated for florfenicol were found to be 5,360 in intestine, 2,890 in gill, 2,250 in kidney, 973 in liver and 273 in plasma, obtained at Tmax of 16 h. Intestine had utmost area under the concentration–time curve (tissue/plasma) of 13.83 h μg kg−1 and a prolonged half life (t1/2ß) of 28.62 h. The highest apparent metabolic rate value in the kidney (0.327) showed a high level of biotransformation of florfenicol to its metabolite florfenicol amine. The apparent distribution rate of florfenicol amine in muscle, in comparison to the parent drug florfenicol, indicated elimination of the medication mostly in the form of florfenicol amine with t1/2 of 16.75 h. The biosafety of florfenicol orally administered to rainbow trout recorded effective feed consumption, physiological responses, drug tolerance and significantly low drug concentrations in muscle of rainbow trout, thus its usage at 10 mg kg−1 fish body weight is recommended. In the study, the rapid absorption, greater bioavailability, enhanced dispersion, slower elimination and biosafety of the drug form a significant basis for the florfenicol and its metabolite florfenicol amine as a useful antibacterial agent in aquaculture.